Production systems of swine in the rural areas of Rangamati and Khagrachari districts of Bangladesh (Bangladesh Journal of Animal Science, 2012)
The study was undertaken for a period of 60 days to investigate the production systems of swine in Rangamati and Khagrachari districts, Bangladesh. Production systems, particularly housing, feeding, breeding, disease prevalence, vaccination, bio-security, marketing, socio-economic condition and constraints of pig production were investigated during the study period. It was found that the propensity of rearing pig differed significantly (P